IFLA cataloguing principles : steps towards an international cataloguing code, 5 ; report from the 5th IFLA Meeting of Experts on an International Cataloguing Code, Pretoria, South Africa, 2007 - Tillett, Barbara B.; International Federation of Library Associations and Institutions (Munchen : K. G. Saur, 2008)
Volume 35 of the IFLA Series on Bibliographic Control is the report of the fifth and final meeting of the IME ICC.
Includes bibliographical references.
Text in English, some papers with French and Portuguese translations.
rua 11/10/13
Loans
Keywords: Descriptive cataloguing -- Standards -- Congresses; Cataloguing; Bibliographic control; IFLA